2021
DOI: 10.1007/s10856-021-06578-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and evaluation of antibacterial activity of transition metal oxyde nanoparticles

Abstract: Nanoparticles (NPs) have a wide range of applications in various areas. For health application, cytotoxicity tests are used to ensure its efficiency and safety. In this paper, ZnFe2O4, CoFe2O4, Zn0.5Co0.5Fe2O4 NPs were synthesized, characterized and their antibacterial properties were evaluated. The Sol-Gel method was used to synthesize the NPs. Their electronic and crystallographic structures were characterized by Fourier Transform Infrared Spectroscopy Analysis (FTIR), X-ray fluorescence (XRF), X-Ray Diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…In the case of copper, the photoelectron peaks of Co 2p split into Co 2p 3/2 and Co 2p 1/2 with binding energies at 778 and 794.9 eV, respectively, confirming the presence of Co 2+ and Co 3+ in the sample. These information corroborate well with that of the Reitveld refinement for cobalt ion occupancy at the B site. , For nickel, the Ni 2p 3/2 exhibits the existence of three peaks at 854.06, 855.63, and 860.4 eV attributing to Ni 2+ , Ni 3+ , and the satellite peak, respectively. This confirms the +3 oxidation state of nickel. , The survey spectra confirm the presence of Zn, Fe, O, Co, and Ni in the synthesized samples.…”
Section: Resultssupporting
confidence: 87%
“…In the case of copper, the photoelectron peaks of Co 2p split into Co 2p 3/2 and Co 2p 1/2 with binding energies at 778 and 794.9 eV, respectively, confirming the presence of Co 2+ and Co 3+ in the sample. These information corroborate well with that of the Reitveld refinement for cobalt ion occupancy at the B site. , For nickel, the Ni 2p 3/2 exhibits the existence of three peaks at 854.06, 855.63, and 860.4 eV attributing to Ni 2+ , Ni 3+ , and the satellite peak, respectively. This confirms the +3 oxidation state of nickel. , The survey spectra confirm the presence of Zn, Fe, O, Co, and Ni in the synthesized samples.…”
Section: Resultssupporting
confidence: 87%
“…coli) where Gram-positive bacteria were more vulnerable to doped-IONPs than Gram-negative bacteria (Figure ). Additionally, the ZOI produced for ZnFe 2 O 4 nanoparticles was slightly larger than that for low-temperature calcined nanoparticles. This means that low-temperature calcined nanoparticles crystalline structure was moderately more efficient in inhibiting both strains .…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 85%
“…A study by Morais et al (2021) showed that ZnFe 2 O 4 , CoFe 2 O 4 , and Zn 0.5 Co 0.5 Fe 2 O 4 exhibited antimicrobial activity against Gram-positive (Staphylococcus aureus) and Gram-negative bacteria (E. coli) where Gram-positive bacteria were more vulnerable to doped-IONPs than Gram-negative bacteria (Figure ).…”
Section: Doped-iron Oxide Nanoparticles (Doped-ionps)mentioning
confidence: 99%
See 2 more Smart Citations